2022
DOI: 10.18502/ijrm.v20i7.11561
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consuming evening primrose oil on cervical preparation before hysteroscopy: An RCT

Abstract: Background: Herbal medicine could be effective at treating various illnesses. Hysteroscopy can be an effective method for assessing the uterus in terms of anatomical, physiological and pathological anomalies. Objective: This study aims to evaluate the effect of evening primrose oil (EPO) on cervical preparation in women candidates for hysteroscopy. Materials and Methods: This study was a double-blind, randomized controlled clinical trial including 160 women candidates for diagnostic hysteroscopy wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The results of a study by Mansour Ghanaei et al 19 of 160 female candidates for diagnostic hysteroscopy showed that the mean Hegar size in women receiving two softgels of 500-mg EPO vaginally 6 hours before the procedure was significantly higher than the placebo group. No side effects such as uterine rupture, cervical rupture, diarrhea, nausea, or abdominal pain were observed in the EPO group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a study by Mansour Ghanaei et al 19 of 160 female candidates for diagnostic hysteroscopy showed that the mean Hegar size in women receiving two softgels of 500-mg EPO vaginally 6 hours before the procedure was significantly higher than the placebo group. No side effects such as uterine rupture, cervical rupture, diarrhea, nausea, or abdominal pain were observed in the EPO group.…”
Section: Discussionmentioning
confidence: 99%
“…The results of multiple studies showed that EPO is effective in preparing the cervix before gynecological surgery 13,17–19 . EPO has been suggested as an alternative treatment to improve women's health due to its convenience and cost‐effectiveness, 19 but research in this field is limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatherapy which uses essential oil derived from plants, is a complementary and alternative medicine 13 . There has been a lot of research on anxiolytic properties of Lavandula angustifolia , Rosa damascene , and Osmanthus fragrans 14,15 . Lemon verbena (LV) belongs to the lemon verbenaceae family so its leaves have lemon odor and flavor.…”
Section: Introductionmentioning
confidence: 99%
“… 13 There has been a lot of research on anxiolytic properties of Lavandula angustifolia , Rosa damascene , and Osmanthus fragrans . 14 , 15 Lemon verbena (LV) belongs to the lemon verbenaceae family so its leaves have lemon odor and flavor. This plant was initially cultivated in Central and South America and was transferred to Europe in the 17th century.…”
Section: Introductionmentioning
confidence: 99%